Correlating Isavuconazole Serum Levels with Efficacy and Adverse Effects (AE) Among Immunocompromised Patients. (4th October 2017) - Kim, Pauline; Tegtmeier, Bernard; Dadwal, Sanjeet; Ito, James; Kriengkauykiat, Jane
Abstract: Background: Isavuconazole (ISV) is an antifungal approved for treatment of invasive aspergillosis and mucormycosis. Although data correlating response to serum levels is lacking, we found in a previous report a trend towards increased side effects with elevated serum trough levels. This study expands to a larger population to evaluate ISV trough levels in relation to clinical outcomes and side effects (AE). Methods: Patients who received ISV >/ = 7 days with serum trough levels from April 2015 to September 2016 were included in AE analysis. Patients with proven or probable invasive fungal infection (IFI) were evaluated for response. Demographics, ALT, total bilirubin, serum creatinine, QTc, 14-, 30-, and 90-day response (complete, partial or no response) were collected. Results: 94 patients were evaluated for response. At baseline, 39% were female, 70% had leukemia, 55% had hematopoietic cell transplant (87% were allogeneic), and 73% had active disease (relapsed, progressing, newly diagnosed). Of the IFIs, 64% were due to Aspergillus species, 12% Mucorales, and 4% Fusarium species. Response rates for patients by trough levels <3 vs. 3 to 5 vs. >5 mcg/mL are as follows: 14-day was 32% vs. 32% vs. 25%, 30-day was 48% vs. 52% vs. 44%, and 90-day was 39% vs. 50% vs. 33%, all P =  NS. 205 patients were evaluated for AE in relation to trough levels. In comparing patients with trough levels <5 vs. >/ = 5 ug/mL, ALT levels 3 times upper limit was 18% vs. 36% ( P = 0.032), total bilirubin 3 times upper limit was 22% vs. 32% ( P = 0.79), serum creatinine 3 times upper limit was 7.8% vs. 12% ( P = 0.47), and QTc interval was 1% vs. 2% mean decrease from baseline ( P =  0.9). Conclusion: Higher ISV levels were associated with increased ALT. ISV levels did not show apparent correlation with response rates, but there is a trend towards improved response rates with ISV levels between 3 - 5 ug/mL. Disclosures: S. Dadwal, Merck: Investigator, Research support. GlaxoSmithKline: Investigator, Research support. Ansun Biopharma: Investigator, Research support. Oxford Immunotec: Investigator, Research support. Gilead Sciences: Investigator, Research support. J. Ito, Astellas: Speaker's Bureau, Speaker honorarium.